Implementing and administering Cisco Solutions: 200-301 : CCNA Exam Guide - Singh, Glen D., ....- (Birmingham : Packt Publishing, 2020)
In the dynamic technology landscape, staying on top of the latest technology trends is a must, especially if you want to build a career in network administration. Achieving CCNA 200-301 certification will validate your knowledge of networking concepts, and this book will help you to do just that. This exam guide focuses on the fundamentals to help you gain a high-level understanding of networking, security, IP connectivity, IP services, programmability, and automation. Starting with the functions of various networking components, you'll discover how they are used to build and improve an enterprise network. You'll then delve into configuring networking devices using a command-line interface (CLI) to provide network access, services, security, connectivity, and management. The book covers important aspects of network engineering using a variety of hands-on labs and real-world scenarios that will help you gain essential practical skills. As you make progress, this CCNA certification study guide will help you get to grips with the solutions and technologies that you need to implement and administer a broad range of modern networks and IT infrastructures. By the end of this book, you'll have gained the confidence to pass the Cisco CCNA 200-301 exam on the first attempt and be well-versed in a variety of network administration and security engineering solutions.